2018
DOI: 10.1159/000488436
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27a Promotes Hemin-Induced Erythroid Differentiation of K562 Cells by Targeting CDC25B

Abstract: Background/Aims: MicroRNAs (miRNAs) play a crucial role in erythropoiesis. MiR-23a∼27a∼24-2 clusters have been proven to take part in erythropoiesis via some proteins. CDC25B (cell division control Cdc2 phosphostase B) is also the target of mir-27a; whether it regulates erythropoiesis and its mechanism are unknown. Methods: To evaluate the potential role of miR-27a during erythroid differentiation, we performed miR-27a gain- and loss-of-function experiments on hemin-induced K562 cells. We detected miR-27a expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In the human genome, miRNAs regulate protein encoding genes at a rate of approximately 1:3, controlling cell apoptosis, proliferation, differentiation, metabolism, individual development and tumorigenesis, and drug resistance . Target gene expression is regulated by two mechanisms: (i) binding to the untranslated region (3'UTR) of the target messenger RNA (mRNA) 3' end, inhibiting its translation; and (ii) like small interfering RNA (siRNA), miRNA binds to the target and degrades target mRNA . Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human genome, miRNAs regulate protein encoding genes at a rate of approximately 1:3, controlling cell apoptosis, proliferation, differentiation, metabolism, individual development and tumorigenesis, and drug resistance . Target gene expression is regulated by two mechanisms: (i) binding to the untranslated region (3'UTR) of the target messenger RNA (mRNA) 3' end, inhibiting its translation; and (ii) like small interfering RNA (siRNA), miRNA binds to the target and degrades target mRNA . Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Target gene expression is regulated by two mechanisms: (i) binding to the untranslated region (3'UTR) of the target messenger RNA (mRNA) 3' end, inhibiting its translation; and (ii) like small interfering RNA (siRNA), miRNA binds to the target and degrades target mRNA. [17][18][19] Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers. [20][21][22][23][24] In recent years, abnormal expression of miR-873 has been found in many kinds of tumors, such as breast and ovarian cancers, and glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Also, erythroid cells at successive terminal stages of human erythropoiesis were also identified by using the combination of glycophorin A (GPA) and Band 3 ( Auffray et al., 2001 ; Hu et al., 2013 ). Toward this end, we used hemin at 50 μM to treat human erythroleukemic K562 cells as a cellular model for erythroid differentiation induction, as indicated by benzidine staining-positive (DAB + ) cells (an indicator for Hb production) and accumulation of HbG ( Rutherford et al., 1979 ; Wang et al., 2018 ). More intriguingly, our results demonstrated that FAM122A mRNA and protein levels were gradually decreased upon hemin-induced erythroid differentiation ( Figures S1 A, 1 B, and 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KLF3 could suppress the expression of miR-23a27a24-2 cluster (named as miR-23a cluster) by binding to the CACCC sites in the promoter of miR-23a cluster, miR-23a cluster and KLF3 formed a positive feedback loop to promote β-like globin expression during erythropoiesis [40]. Meanwhile, miR-27a promotes hemin-induced erythroid differentiation of K562 cells by targeting CDC25B [41].…”
Section: Mir-23a / Mir-27a / Mir-24mentioning
confidence: 99%